Alignments and network of graphite fillers to improve thermal conductivity of epoxy-based composites. (October 2015) - Burger, N.; Laachachi, A.; Mortazavi, B.; Ferriol, M.; Lutz, M.; Toniazzo, V.; Ruch, D.
Highlights: Large inter-particles distances reduce thermal conductivity. Structured composites by networks or alignments of particles help increasing thermal conductivity. The more filler/matrix interfaces, the lower the thermal conductivity. Abstract: Instead of improving the fillers dispersion in the matrix, some fillers alignments and structured composites were investigated in order to highlight their impact on thermal conductivity. Whereas well dispersed graphite-nanocomposites show some limit to reach high thermal conductivity values (0.84 W m −1  K −1 at 12 wt.%), 3D-structured composite or Z-pinning samples display much better enhancements of apparent thermal conductivity, reaching 2.1 W m −1  K −1 at 15 wt.%. Impact of insulating DGEBA interfaces was also investigated in this work. It was demonstrated that only two 4 μm-DGEBA layers cutting the fibers alignment is enough to bring thermal conductivity back to the value of the non-structured nanocomposite, losing all the positive impact of alignment. Mathematical evaluations helped estimating the through-plane thermal conductivities of the samples, highlighting the negative impact of interfaces, and displaying the major difference between a 3D-network sample and a Z-pinned aligned sample. Whereas the 3D-network sample displays a relatively good improvement of both in-plane and through-plane thermal conductivities, the Z-pinned sample presents a considerable increase of the through-plane thermal conductivity (until 6.8 W m −1  K −1 ), but also a negligible effect on the in-plane thermal conductivity. Resulting apparent thermal conductivities of both samples are finally quite comparable and more than doubled compared to non-structured nanocomposites.